PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK BERBANTUAN E-BOOK MAKER PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS II SD - Ridani Amalia; Dinda Yarshal (STKIP Subang, 2026)
This study aims to develop digital-based learning media in the form of flipbooks supported by the E-Book Maker application (Heyzine Flipbooks) in the Pancasila Education subject for grade II Elementary Schools, focusing on the material